Peran Pendidikan Agama Kristen dalam Membangun Budaya Damai dan Resolusi Konflik di Kalangan Remaja - Nofita R. Asbanu; Daud Saleh Luji (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
Adolescents are an age group that is vulnerable to social conflict due to emotional immaturity and the search for self-identity. Amidst the increasing cases of violence and intolerance among adolescents, Christian Religious Education (PAK) has strategic potential in forming peaceful characters and constructive conflict resolution skills. This study uses a descriptive qualitative approach through an in-depth literature review of various literature and scientific journals from the last five to ten years. The results of the study indicate that PAK plays a role in internalizing the values ​​of love, forgiveness, tolerance, and justice that are relevant to building a culture of peace. In addition, PAK also contributes to forming a healthy social identity among adolescents, strengthening multicultural awareness, and providing skills in resolving conflicts non-violently. The instillation of these values ​​is carried out through a holistic approach that includes cognitive, affective, and practical learning. Christian Religious Education not only forms religious understanding, but also plays a role as a means of social transformation amidst the complex reality of conflict. Thus, PAK can be an important element in efforts to prevent conflict and form a young generation with a peaceful personality. These findings are expected to be the basis for developing a curriculum and practice of Christian education that is more responsive to the social challenges faced by today's youth.